Short-acting β2-agonist prescription patterns and clinical outcomes in Malaysia: A nationwide cohort of the SABINA III study - Ban, Andrea Yu-Lin; Vengadasalam, Paranthaman; Taher, Sri Wahyu; Mohd Zim, Mohd Arif; Aflah, Syazatul Syakirin Sirol; Daut, Ummi Nadira; Ali, Irfhan Ali Hyder; Pereirasamy, Lalitha; Omar, Azza; Ibrahim, Aishah; Mohd Tarekh, Noor Aliza; Chan, Swee Kim; et al. (Academy of Family Physicians of Malysia, 2023)
Introduction: SABINA III assessed short-acting β2-agonist (SABA) prescription patterns and their association with asthma-related outcomes globally. Herein, we examined SABA prescription and clinical outcomes in the Malaysian cohort of SABINA III. Methods: In this observational, cross-sectional study, patients (≥12 years) were recruited between July and December 2019 from 15 primary and specialty care centres in Malaysia. Prescribed asthma treatments and severe exacerbation history within 12 months prior and asthma symptom control during the study visit were evaluated. Associations of SABA prescription with asthma control and severe exacerbation were analysed using multivariable regression models. Results: Seven hundred thirty-one patients (primary care, n=265 [36.3%]; specialty care, n=466 [63.7%]) were evaluated. The prevalence of SABA over-prescription (≥3 SABA prescriptions/year) was 47.4% (primary care, 47.1%; specialty care, 47.6%), 51.8% and 44.5% among all patients and patients with mild and moderate-to-severe asthma, respectively. Altogether 9.0% (n=66) purchased SABA without a prescription; among them, 43.9% (n=29) purchased ≥3 inhalers. The mean (standard deviation) number of severe asthma exacerbations was 1.38 (2.76), and 19.7% (n=144) and 25.7% (n=188) had uncontrolled and partly controlled symptoms, respectively. Prescriptions of ≥3 SABA inhalers (vs 1-2) were associated with lower odds of at least partly controlled asthma (odds ratio=0.42; 95% confidence interval [CI]=0.27-0.67) and higher odds of having severe exacerbation(s) (odds ratio=2.04; 95% CI=1.44-2.89). Conclusion: The prevalence of SABA over-prescription in Malaysia is high, regardless of the prescriber type, emphasising the need for healthcare providers and policymakers to adopt latest evidence-based recommendations to address this public health concern. © 2023, Academy of Family Physicians of Malaysia. All rights reserved.